Review of Potential Biochar Utilization on Soil Quality in Agricultural Environments - Badrus Zaman; Anik Sarminingsih; Lisa Cahya Pratiwi (Postgraduate, University of Mataram, 2023)
Land and environmental sustainability are two interconnected factors of long-term development. Former sand mining area that has been neglected and disused for many years can have a significant impact on environmental degradation. Sand mining activities previously conducted on this site employing trucks hauling mining goods may have had an impact on soil erosion and topsoil removal. The use of biochar is one promising invention in agriculture and land restoration. The purpose of this article is to investigate the usage of biochar as a substance for enhancing soil quality. Biochar is a carbon product derived from the pyrolysis (low or no oxygen heating) of organic biomass such as wood, straw, or other plant leftovers. Because of its numerous benefits in enhancing soil quality and promoting sustainable agriculture, the use of biochar in agriculture and land restoration has attracted extensive attention. Aside from that, biochar is thought to be more efficient than other techniques of enhancing soil quality due to its low cost